'Buildup Minimizing Assembly': a system to minimize the buildup effect in γ-ray attenuation measurements as a laboratory experiment. (1st June 2016) - Adamides, E; Kavadjiklis, A; Koutroubas, S K; Moshonas, N; Tzedakis, A
Abstract: We have constructed an apparatus we call 'Buildup Minimizing Assembly' (BMA), which can be used to achieve narrow beam, good geometry characteristics in γ -ray attenuation measurements, thus minimizing the buildup contribution. The apparatus is easy to construct and can be implemented in undergraduate laboratory experiments. Here we have applied it with lead and iron absorbers in our experiments with excellent results.